국내 실내공기질 관리정책의 변천 및 제어기술의 현황 - 배귀남; 지준호 (한국대기환경학회, 2013)
In Korea, studies on the indoor air quality have been conducted since mid of 1980s. The turning point occurred in 2003 by establishing the act of the indoor air quality management for public facilities. According to the law, the basic plan for indoor air quality management is prepared by government every five years, affecting greatly governmental policy and related academia and industries. Indoor air quality survey was mostly carried out among indoor air quality researches. After then, assessment of health effect and air cleaning technology were studied. Although various control technologies for particle, bioaerosol, odor, and hazardous chemicals have been applied to indoor environments, breakthrough technologies are needed to solve real problems facing at the applied environments. In the future, issue of indoor air quality is more interested and both management policy and control technology are key factors in order to realize comfort and healthy indoor environments.